Debugging the case for creationism. - Grafton-Cardwell, Patrick (Philosophical Studies, 2020)
Repeatable artworks like musical works have presented theorists in the ontology of art with a puzzle. They seem in some respects like eternal, immutable objects and in others like created, historical objects. Creationists have embraced the latter appearances and attempted to compel Platonists to follow them. I examine in detail each argument in a cumulative case for Creationism, showing how the Platonist can respond. The conclusion is that the debate between Platonists and Creationists is a stalemate. In order for progress to be made in the first-order debate, second-order progress on the metaontology of art needs to come first.